Analysis of Some Selected Toxic Heavy Metals in Some Branded Nigerian Herbal Products - Ekeanyanwu R.C., Njoku J.O., Nwodu P.O., Njokuobi A.E (Journal of Applied Pharmaceutical Science, 2013)
The use of herbal medicine has been in the increase in many developing and developed nations and Nigeria in particular has been using herbal medicine for many centuries. The approval of these herbal remedies by regulatory bodies has further encouraged the use of herbal remedies. The safety of these herbal remedies is however poorly understood. The present study was designed to estimate the concentration of heavy toxic metals in branded Nigerian herbal products frequently used for treatment of various ailments. Nine brands of herbal medicines were selected for the analysis of trace metals quality using Atomic Absorption Spectrometer. The samples were prepared for analysis by wet digestion method using nitric acid and perchloric acid treatment and then analysed using a flame Atomic Absorption Spectrometer. The contents of Copper, Manganese and Cadmium were below toxic limits in all the samples analysed. However, Chromium and Nickel were not detected in the samples. There is need for continuous monitoring of branded herbal drugs sold in the market to ensure wholesome and safe herbal drugs are sold for human consumption.
Keywords: Copper, Manganese, Chromium, Cadmium, Nickel, Toxici